Knowledge, attitude, and psychological effect on undergraduate/postgraduate students in Lockdown COVID-19 situation - Santosh Kumar Verma; Barun Dev Kumar; Subhash Chandra; Neha Singh; Priyanka Kumari; Abhishek Verma (Wolters Kluwer Medknow Publications, 2021)
Background: Student psychological health has been an increasing concern. The COVID-19 pandemic situation has brought this vulnerable population into renewed focus. Objective: Our study aims to conduct a timely assessment of the effects of the COVID-19 pandemic on the mental health of college graduates and postgraduates. Methodology: We conducted online survey with 550 students to understand the effects of the pandemic on their psychology and well-being. The data were analyzed through quantitative and qualitative methods. Results: Of the 550 students, 138 (71%) indicated increased stress and anxiety due to the COVID-19 outbreak. When asked about how the lockdown in COVID-19 situation affecting them, 97% said that it is severely affecting them. When asked about what the problems do you faced during online class, 5% said the Internet, 83.8% said noninteractive, and 11.2% said lack of explanatory mediums. When asked about number of hours spent on the Internet, 100% said more than 10 h. When asked about the activities to keep yourself busy during lockdown in COVID-19 situation, 37% said social media followed by 23% who mentioned cooking. Conclusion: Due to the long-lasting pandemic situation and onerous measures such as lockdown and stay-at-home orders, the COVID-19 pandemic brings negative impacts on education. The findings of our study highlight the urgent need to develop interventions and preventive strategies to address the psychological health of college students.